Analysis Of Workload And Emotional Intelligence In Enhancing Employee Performance At Permata Cirebon Hospital Through The Mechanisms Of Adaptation - Setiawan, Mira Utami; Sunarya, Erry; Suwiryo, Darmo H. (Universitas Muhammadiyah Pontianak, 2025)
This study aims to examine the effect of workload and emotional intelligence on employee performance with the mediating role of adaptation mechanisms at Permata Cirebon Hospital. The method used is quantitative method with Structural Equation Modeling (SEM) technique, involving 200 respondents. The results show that workload has a negative effect on performance, while emotional intelligence has a significant positive effect. Adaptation mechanisms proved to significantly mediate the relationship between the two variables on employee performance. The findings confirm the importance of managing workload, developing emotional intelligence, and strengthening adaptability as strategies to improve employee performance in a sustainable manner.